PROSEDUR PEMASANGAN BARU ALIRAN LISTRIK PADA PT. PLN (PERSERO) RANTING MARIANA - Erdiansyah, Erdiansyah (Jurnal Media Wahana Ekonomika, 2011)
Some of these obstacles that lead to the length of the new installation of electricity, which PT PLN (Persero) Branch Mariana have to wait for shipment of materials from PT PLN (Persero) Branch for the new installation of electricity or for the manufacture of a new network overloading the network. But the amount of time and materials to be accepted pengirirman PT PLN (Persero) Branch Mariana determined by PT PLN (Persero) Branch, but PT PLN (Persero) branch does not know when material is required by PT PLN (Persero) Branch Mariana , this is because at the time of the Customer Service PT PLN (Persero) Branch Mariana fill out a new installation of electricity demand is made in just one duplicate and used as an archive PT PLN (Persero) Branch   Mariana  so that no system of accounting information between      PT. PLN (Persero) Branch Mariana by PT PLN (Persero) Branch of material needs. Key words: Procedures, Accounting Information Systems